Analisis Penurunan Penjualan Dodol pada UMKM di Bojong Gede Kabupaten Bogor - Arnes Faradilla; Wawan Kurniawan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Dodol is one of the many products produced by MSMEs in the Bogor district, one of which is Dodol Hj. Muhaya. For several years, especially due to the Covid-19 pandemic, sales turnover has decreased. In addition, the process of rolling Dodol still uses the manual method, so the process takes a long time and the shape is not uniform. This research aims to design a strategy using the Blue Ocean Strategy approach with a four-step framework analysis. Based on the results of the study, it was found that the create factor was the most widely used, namely creating the latest brand packaging and stickers so that consumers were more interested so that it was expected to increase sales of Dodol.